SDK4ED: A platform for technical debt management. (4th May 2022) - Ampatzoglou, Apostolos; Chatzigeorgiou, Alexander; Arvanitou, Elvira Maria; Bibi, Stamatia
Abstract: Technical debt management is of paramount importance for the software industry, since maintenance is the costlier activity in the software development lifecycle. In this article, we present the SDK4ED platform that enables efficient technical debt management (i.e., measurement, evolution analysis, prevention, etc.) at the code level, and evaluate its capabilities in an industrial setting. The SDK4ED platform is the outcome of a 3‐year project, including several software industries. Since, the research rigor of the approaches that reside in SDK4ED have already been validated, in this work we focus: (a) on the presentation of the platform per se; (b) the evaluation of its industrial relevance; (c) the usability of the platform; as well as (d) the financial implications of its usage.